Guia interativo para auxiliar professores no ensino de língua espanhola para pessoas com deficiência visual mediado por tecnologias digitais - Barros, Jennipher Stephanie dos Reis (2024)
The education has experienced significant transformations over the years, driven by social and technological advancement. Currently, there is a tendency to adopt more flexible pedagogical practices. In particular, foreign language teaching faces challenges regarding the inclusion of people with visual impairments, who often encounter barriers in conventional reading and writing practices. In this context, Digital Information and Communication Technologies (DICT) emerge as facilitators by integrating new languages into the educational environment and promoting greater autonomy, participation and activity among blind or visually impaired students. This study aimed to develop a Software Analysis Guide for language teachers, with the aim of diversifying teaching methodologies and strengthening inclusion. The methodology adopted was divided into four stages: 1) writing a Systematic Literature Review, covering research from the last 10 years; 2) application of questionnaires and semi-structured interviews with 24 Spanish teachers from the State Education Network; 3) manual analysis of the software mentioned in the interviews, focusing on accessibility criteria; and 4) creation and evaluation of the Guide. The proposed product provides examples of language teaching activities that use software and presents accessibility assessments, helping teachers make decisions and choose the most appropriate software and activities. An evaluation of the Guide was carried out by five Spanish teachers who participated in the previous phases of the study. They all recognized that the Guide contributes positively to teaching practice and would recommend it to other colleagues interested in integrating language teaching with accessibility.